'Nickel Allergy' arising from decorative nickel plated and alloyed articles: prevention at source. (4th March 2019) - Whittington, C. M.; Lo, W. Y.
ABSTRACT: This work builds on papers published in Transactions during 2015 and 2018 reporting research into low-cost commercial methods for the prevention of nickel release from decorative nickel plated articles, rendering them suitable for placement on the European market in accordance with the requirements of REACH. 'Nickel Allergy' sometimes occurs when nickel-containing articles are in direct and prolonged contact with the skin, leading to corrosion of elemental nickel by sweat, liberating sufficient nickel ions to be absorbed through the skin and initiate an allergenic effect. The EU 'Nickel Restrictions' impose limits on the amount of nickel released from articles intended for use in this application, but permits a non-nickel surface coating that can ensure the rate of nickel release does not exceed 0.5 µg cm −2 week −1 after 2 years of normal use. The official tests for coated items are simulated wear and corrosion under EN 12472 followed by determination of nickel release under EN 1811. Earlier work concluded that suitable barrier coatings over bright electrodeposited nickel are regular chromium deposited from a hexavalent electrolyte, microporous trivalent chromium from a chloride electrolyte and UV cured PU electrophoretic coatings. Further tests reported here focused on nickel release from examples of wearable articles such as costume jewellery and watch cases. A typical flash coating of gold over bright nickel is thin and porous and being more noble, causes the rate of nickel release to be accelerated; but this can be prevented by an intermediate barrier coating of electrodeposited palladium. To round out the relevance of this study on wearable articles, nickel release tests were also conducted on nickel-containing Grades 304 (UNS S30400) and 316 (UNS S31600) austenitic stainless steels, plus a typical gold alloy containing nickel. All passed the nickel release tests satisfactorily.